Improvement of the computer complex for adaptive electrical stimulation taking into account arthroscopy data - Shapoval, Y.; Prasol, I. (ХНУРЕ, 2025)
The features of the construction of a biotechnical complex for adaptive electrical stimulation of human muscles are considered. The selection of stimulating signals of different contractility is carried out taking into account the individual state of the human neuromuscular apparatus. The complex allows monitoring the effectiveness of rehabilitation procedures by registering the electromyogram signal, matching the parameters of the electrical stimulation signal with the characteristics of the muscles, as well as with the data of diagnostic arthroscopy.
Keywords: electrical stimulation; arthroscopy data